Strategi Meningkatkan Partisipasi Anak dalam Kegiatan Olahraga di PAUD - Ninit Averiana Fahdan; Rivan Saghita Pratama (Khirani: Jurnal Pendidikan Anak Usia Dini, 2025)
Sports play a crucial role in supporting early childhood development, including physical, cognitive, and socio-emotional growth. However, participation in sports activities in early childhood education (PAUD) is often low. This article aims to identify the factors influencing children's participation in sports and develop strategies to enhance their involvement. The method used is a literature review of various studies related to child development, the benefits of sports, and factors supporting early childhood sports participation. The findings indicate that interest, motivation, parental support, environment, and the availability of facilities are key factors influencing participation. Strategies to enhance participation include creating a fun environment, providing varied activities, positive support from teachers, and active parental involvement. Structured and flexible implementation of sports programs in PAUD is essential to establish healthy habits from an early age.